Exhaust steam for biomass drying - Potential efficiency enhancement of palm oil mill cogeneration plant - Abd Majid, M.A. (Asian Research Publishing Network, 2018)
Most of the local palm oil mill cogeneration plants in Malaysia were built 20 years ago. Since the boilers were designed for the purpose to burn the biomass residue, the efficiencies of these plants are low. With the current emphasis by the government to exploit the use of biomass for renewable energy, the plant owners realised that their plants could benefits if the plants efficiencies are enhanced through biomass drying using the exhaust steam. By drying of biomass residue the thermal energy that could be generated by the plants could be increased and thus increasing of available power which could be sold to the grid. This study assessed this potential. The data of existing cogeneration was used to evaluate the additional energy that could be generated by dried biomass, which is dried using the exhaust steam from the steam turbine. Based on the mill capacity of 20 ton/hr, 30 ton/hr and 45 ton/hr respectively, it was estimated thermal energy that could be made available to dry the biomass are 3.46 ton/h, 2.96 ton/hr, 4. 44 ton/hr. respectively. Â© 2006-2018 Asian Research Publishing Network (ARPN).